Extent of Adoption of Intercropping Practices Among Farmers of Haryana (Indian Journal of Extension Education, 2022)
Intercropping is a variant of multiple cropping practices that includes the cultivation of two or more crops in definite close proximity. The current study was led in dry and wet agro climatic zones of Haryana in 2022 with an objective to assess the adoption of intercropping practices among farmers of Haryana. The primary data were collected personally from 120 respondents through a well-structured interview schedule. Findings revealed that nearly three-fifths of the respondents had medium level of adoption of intercropping practices and the farmers were adopting intercropping mainly in vegetables. Highly significant association was found between education, mass media exposure, inheritance with level of adoption of the intercropping system. A significant association was found between age, caste, annual income, land holding, extension contacts with level of adoption. The main reasons for adoption of intercropping were higher income and improved socio-economic status. The paper recommends on field training/demonstration for farmers who were adopting intercropping so that adoption of intercropping can be made efficient and from this more number of farmers will be encouraged to adopt intercropping.